Pro gradu - tutkielma : Hevosavusteisen johtamiskoulutuksen hyödyt - Palo-oja-Mertanen, Katri Johanna (My University, 2024)
The aim of the study was to deepen the understanding of the benefits of equine-assisted leader- ship training in developing self-awareness and emotional intelligence among individuals in leadership positions. At the core of the study were three research questions: How can horses be used to develop a leader ́s awareness of their own and other ́s emotions and their impact on leadership situations? How can horses be used to support a leader in identifying their leadership styles and enhancing their self-assessment skills? How can horses be used to promote the devel- opment of a leader ́s self-confidence in leadership situations? Development of self-awareness is a subjective process that is built through individual ́s own in- terpretations in interaction with horses. Thus, a qualitative research design was considered ap- propriate. Semi-structured interviews and video ethnography were used to study the experiences of leaders in equine-assisted training. The interviews provided a possibility for participant ́s to explain their own experiences and perspectives, while video ethnography allowed for the exami- nation of non-verbal interaction and profound understanding of the dynamics on equine-assisted leadership. The selected methods for data collection included written open surveys, verbally conducted semi-structured interviews, observation and analysis during the research day, and feedback from the equine behaviour trainer. Thematic analysis revealed that experimental leadership training programs are an integral com- ponent of leadership education, providing a valuable platform for the development of leadership skills. This is based on participants' personal experiences and active learning approaches. Equine-assisted leadership training is a form of leadership development where horses are used as partners to facilitate learning about leadership qualities, communication, and emotional intel- ligence through experiential activities. The study contributed with new knowledge about the ef- fects on equine-assisted leadership training on the development of leader ́s behavioural patterns. From the practical perspective, this study demonstrates that while the potential of equine-as- sisted leadership development is recognized, research in this area remains relatively limited.
Keywords: johtaminen; johtajuus; kehittäminen; hevonen; oppiminen; johtamiskoulutus; tunneäly; kokemusoppiminen; itsetuntemus; itseluottamus; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Liiketoiminnan kehittämisen maisteriohjelma|en=Master´s Programme in Business Development|